Optimalisasi Kemampuan Bahasa Inggris Praja IPDN Sulawesi Utara melalui Pelatihan Terpadu Berbasis TOEFL - Hidayati Otoluwa, Moon; Wardatul Jannah Husain, Sabrina; Wardaty Saud, Indah (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2024)
English language proficiency is essential for students of the North Sulawesi Institute of Domestic Government (IPDN) as well as preparing them for their future in governance and international collaboration. However, challenges such as varying basic English language skills and unfamiliarity with standardized tests such as TOEFL hinder their progress. This study aims to optimize the English language proficiency of IPDN students through an integrated training program tailored to the TOEFL framework. Using a pre-test and post-test design, the program features structured modules, TOEFL simulations, and ongoing evaluations over a period of 2 months and 2 weeks. Quantitative data results revealed a significant average increase in TOEFL scores from 450 to 510 with significant improvements across Listening, Structure and Written, and Reading. Qualitative feedback resulted in increased confidence and mastery of test-taking strategies among students. This study underscores the importance of targeted English language training in improving language skills and recommends integrating similar programs into the IPDN curriculum to foster sustainable language development and global competitiveness.